Editorial: Modern Challenges for International Business in Europe - Jacek Klich (Entrepreneurial Business and Economics Review)
Globalisation,  integration,  regionalisation  or  integration  processes  are  indeed  very crucial for local businesses, which more and more often think globally and act locally (Kefalas, 1998), especially in Europe, thus globalisation and Europeanisation processes are currently key contemporary challenges for international businesses in Europe.